Potensi tepung daun sirsak, serai, kenikir, jeruk nipis, dan kluwih terhadap kumbang bubuk kedelai (Callosobruchus analis F.) pada kedelai (Glyxine max L.) dalam simpanan - Laily Dwi Dzulhijja; Wagiyana W; Sigit Prastowo (Jurnal Proteksi Tanaman Tropis, 2020)
This study aims to determine the effect of soursop leaf flour, lemongrass flour, kenikir leaf flour, lime leaf flour, and kluwih leaf flour on: 1) mortality, 2) damage to seeds, 3) shrinkage of seed weight, 4) appearance of adult C. analysts on soybean seeds in deposits and 5) laying eggs of C. analis imago female eggs, 6) probit analysis LT50. The experiment was carried out using a Completely Randomized Design (CRD). As treatments are: A) controls; B) soursop leaf flour in doses of 1 g, 2 g, and 3 g; C) Serai leaf flour with doses of 1 g, 2 g, and 3 g; D) kenikir leaf flour with doses of 1 g, 2 g, and 3 g; E) lime leaf flour with doses of 1 g, 2 g, and 3 g; and F) kluwih leaf flour with doses of 1 g, 2 g, and 3 g. Each treatment uses five replications. The observed parameters were analyzed by "F" test variance then if it was significantly different to find out the difference in the effect of treatment, an Tukey HSD Test was conducted at a level of 5% distrust. The best mortality results using the treatment of soursop leaf flour dose 3 g on 5 days amounted to 1.80 tails; 1 month is 6.60; 2 months totaling 13.40; and 3 months totaling 11.20. The results of the observation of the number of eggs produced by C. analis the best analyst was the treatment of soursop leaf flour dose 3 g on 5 days amounting to 139 items, 1 month 119.20 items; 2 months 91.20 items; and 3 months 72.20 items. The best imago observation results were treatment of soursop leaf flour dose 3 g at 1 month amounting to 132.20 tails; while at 2 months there were 79 heads. The best observation of seed damage and shrinkage of seed weight was the treatment of soursop leaf flour with a dose of 3 g, in the damage of seeds of 67.40 grains of seed damage; while the seed weight is reduced by 17.94 g. The results of the best analysis of Probit LT50 were treatment of soursop leaf flour with a dose of 3 g because it could kill 50% of the population C. analis with a relatively short time were 9 days after treatment.